2008
DOI: 10.1080/01443610802043066
|View full text |Cite
|
Sign up to set email alerts
|

The effects of estrogen therapy and estrogen combined with different androgenic progestins on carbohydrate and lipid metabolism in overweight–obese younger postmenopausal women

Abstract: Estrogen therapy had a positive effect on carbohydrate and lipid metabolism in overweight-obese postmenopausal women. The addition of progestin to estrogen therapy attenuated estrogen's positive effects slightly; however, the biological actions of the three different androgenic progestins used did not result in any variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Thus, the interruption of gonadal estrogen se- cretion, with the consequent androgen/estrogen imbalance, favors abdominal fat deposition with increased visceral fat [30,31]. In other studies, it has been reported that this deficiency is related to body weight gain and development of obesity in adult humans, mice and the OVX hamster [32][33][34].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the interruption of gonadal estrogen se- cretion, with the consequent androgen/estrogen imbalance, favors abdominal fat deposition with increased visceral fat [30,31]. In other studies, it has been reported that this deficiency is related to body weight gain and development of obesity in adult humans, mice and the OVX hamster [32][33][34].…”
Section: Discussionmentioning
confidence: 97%
“…Deficiency or loss of estrogens in adult animals, e.g. in follicle-stimulating hormone receptor knock out mice [20], ovariectatomied (Ovx) mice and Syrian hamster [21-24], and aromatase knock out (ARKO) mice [16-18], is associated with bodyweight gain and the development of obesity. Furthermore, more interestingly, Gao et al [19] reported that estrogens regulated the body weight and energy metabolism in the brain in a way similar to that of the leptin, the hormone that regulates energy metabolism in the brain.…”
Section: Role Of Estrogens Estrogenic Chemicals and Ers In Obesitymentioning
confidence: 99%
“…The increase in adiposity is likely due to the decline in endogenous estrogens [20]. On the other hand, estrogen therapy has positive effects on carbohydrate and lipid metabolism in overweight-obese younger postmenopausal women [21, 22]. …”
Section: Role Of Estrogens Estrogenic Chemicals and Ers In Obesitymentioning
confidence: 99%
“…Systemic loss of estrogen in postmenopausal women is typically associated with increased abdominal fat tissue. Studies have indicated that estradiol (E2) replacement can prevent menopause induced gains in adipose tissue mass [ 9 10 ]. In addition, ovariectomized (OVX) rodents rapidly become obese; however estrogen administration prevents the increase in body fat [ 11 ].…”
Section: Introductionmentioning
confidence: 99%